Intrapopulation variance in ecophysiological responses to water limitation in a butterfly metapopulation suggests adaptive resilience to environmental variability. Issue 22 (25th October 2022) - Lehmann, Philipp; Wheat, Christopher W.
Abstract : How organisms that are part of the same trophic network respond to environmental variability over small spatial scales has been studied in a multitude of systems. Prevailing theory suggests a large role for plasticity in key traits among interacting species that allows matching of life cycles or life‐history traits across environmental gradients, for instance insects tracking host‐plant phenology across variable environments (Posledovich et al. 2018). A key aspect that remains understudied is the extent of intrapopulation variability in plasticity and whether stressful conditions canalize plasticity to an optimal level, or alternatively if variation in plasticity indeed could increase fitness in itself via alternative strategies. In a From the Cover article in this issue of Molecular Ecology, Kahilainen et al. (2022) investigate this issue in a classical insect study system, the metapopulation of the Glanville fritillary butterfly ( Melitea cinxia ) in the Åland archipelago of Finland. The authors first establish how a key host plant responds to water limitation, then quantify among‐family variation in larval growth and development across control and water‐limited host plants. Finally, they use RNA sequencing to gain mechanistic insights into some of these among‐family differences in larval performance in response to host‐plant variation, finding results suggesting the existence of heritable, intrapopulation variability in ecologically relevant plasticity. This final step represents a critically important and often overlooked component of efforts to predict sensitivity of biological systems to changing environmental conditions, since it provides a key metric of adaptive resilience present in the system.